Degree of phosphate saturation in highly weathered tropical soils - Campos, Murilo de [UNESP]; Antonangelo, Joao Arthur; van der Zee, Sjoerd E. A. T. M.; Ferracciu Alleoni, Luis Reynaldo (Elsevier B.V., 2018)
The degree of phosphate saturation (DPS) is an indicator for P-saturation, which is of assistance to the prediction of P losses and potential eutrophication of surface water. The scaling factor (alpha) estimates the adsorption capacity of the soil and is used to calculate the DPS. In soils from temperate regions, the value of alpha = 0.5 is widely used. However, using just a single value for alpha may fail to estimate the adsorption capacity correctly for all soils. In this study, the aims were (i) to calculate the scaling factor alpha and the DPS of highly weathered tropical soils with different chemical, physical and mineralogical properties in order to predict P losses; and (ii) to identify which soil properties are related to P adsorption. The scaling factor a and the DPS were calculated at 1, 3, 7, 21, 42 and 84 days (d), the highest one in recognition of the long-term kinetics of sorption. The values of alpha increased as the contact period increased. Lower DPS values were obtained in soils with high P adsorption capacity whereas the highest DPS values were obtained in soils with a lower adsorption capacity. Out of ten Oxisols studied, six of them had an a higher than 1. Contents of clay, organic carbon (C) and poorly crystalline (Al-ox) and crystalline (free) Al oxides were the properties that best correlated with P adsorption. For the Oxisols, the clay content, poorly crystalline together with crystalline Fe and Al oxides represented the main components related to P adsorption. The highest DPS (31%) was found in Typic Udorthent. The content of poorly crystalline oxides was not suitable for the scaling factor alpha for most Oxisols, and only the Typic Udorthent exceeded the critical threshold of 23%, and is thus more susceptible to loss of P.
Keywords: Loss of P; Scaling factor alpha; Degree of P saturation; Sorption capacity of P; Principal component analysis